THE 'BASIC POSTULATES' IN PERSPECTIVE. - Metcalf, Richard W. (The Accounting Review, 1964)
The most recent statement of basic postulates of accounting is contained in Accounting Research Study #1, prepared under the auspices of the American Institute of Certified Public Accountants. The 14 postulates presented therein have been grouped under three headings namely environment, field of accounting and imperatives. The attempt to present succinct descriptions of the basic postulates for accounting is meritorious. The philosophy underlying such a project would appear to be directed toward the establishment of a sound foundation for the advancement of accounting theory. However, continued analysis of these and alternative postulates must be undertaken to avoid the creation of a mausoleum from which there could be no escape. A chart has been developed which attempts to depict the interrelationship that appears to exist between these postulates. The heavy reliance upon the deductive process evidenced by this study suggests that a comparable exercise utilizing inductive reasoning should be undertaken for a verification or repudiation of these postulates.